EVALUATION OF THE CRITICAL COMMUNICATION PROCESS IN THE U.S. ARMY FOOD DEFENSE PROGRAM - Sents, Amy (My University, 2014)
According to its website, the United States Army Public Health Command (USAPHC) serves “to promote health and prevent disease, injury and disability in Soldiers and retirees, their family members, and Army civilians, and to assure effective execution of full-spectrum veterinary services for the Army and Department of Defense.” Within this organization, the Veterinary Services Portfolio manages the Animal Medicine and Food Protection Programs. The Health Risk Management Portfolio contains the Health Risk Communication Program, which provides training and consultation services throughout the Department of Defense on how to effectively communicate scientific and technical information to lay persons on an interpersonal level. This report describes the capstone project completed at the interface of the Food Protection Program and the Health Risk Communication Program in order to evaluate the critical communication process that should occur within the U.S. Army Food Defense program. My field experience with the USAPHC, coursework, and supplemental experiences have collectively educated me on and provided me unique experiences with infectious disease control, international trade, border security, weapons of mass destruction, food defense, global health, social behavior, and risk communication.
Keywords: Risk communication; Food defense; Food protection; Anti-terrorism; U.S. Army; Department of Defense; Public Health (0573)